lim (x^2 -2x -3) x->3 lim (x-3)(x+1) x->3 (3-3) (3+1) because its (0) (4).. im not sure whether to times them together so its x=0 or just leave them as x=0 and x=4 thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by fvaras89 lim (x^2 -2x -3) x->3 lim (x-3)(x+1) x->3 (3-3) (3+1) because its (0) (4).. im not sure whether to times them together so its x=0 or just leave them as x=0 and x=4 thanks I don't see the trouble here. The value of the limit is $\displaystyle 3^2 -2(3) - 3 = 0$. That's it. No need for factorsing etc.
yeah, very tempting to factor, but useless afterward because it can be evaluated directly by substitution.
View Tag Cloud